2010
DOI: 10.1007/s10658-010-9682-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification of Fusarium species associated with head blight on wheat in East Croatia

Abstract: Fusarium head blight (FHB) is an important fungal disease of wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…The incidence of wheat head infection by Fusarium culmorum found in the fields in Strzelce (82.1%), Radzików (81.2%) and Kondratowice (80.0%) was quite high compared to other recent studies: 60% in Poland (2007) [5], 19% in Belgium (2007) [7], in Croatia, 29% [8] or 43% in 2009 [13]. However, Goliński et al [28] found F. poae (64%), F. tricinctum (15%), F. avenaceum (8%), F. culmorum (6%) and F. graminearum (4%) as the most common species infecting wheat heads in Poland.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The incidence of wheat head infection by Fusarium culmorum found in the fields in Strzelce (82.1%), Radzików (81.2%) and Kondratowice (80.0%) was quite high compared to other recent studies: 60% in Poland (2007) [5], 19% in Belgium (2007) [7], in Croatia, 29% [8] or 43% in 2009 [13]. However, Goliński et al [28] found F. poae (64%), F. tricinctum (15%), F. avenaceum (8%), F. culmorum (6%) and F. graminearum (4%) as the most common species infecting wheat heads in Poland.…”
Section: Resultsmentioning
confidence: 51%
“…Which Fusarium species is prevalent also depends on other factors, particularly the amount of rain and temperatures at the stage of flowering, but also on agronomic factors, such as soil cultivation, nitrogen fertilization, fungicides, crop rotation, and host genotype [3][4][5][6]. It appears that Fusarium graminearum is most common in moist-warm continental climates, such as Central and South-Eastern Europe [1,2,7,8]. F. culmorum and F. avenaceum are found more often in maritime and cooler European countries [9].…”
Section: Introductionmentioning
confidence: 99%
“…The report on the molecular identification of Fusarium species isolated from naturally infected wheat ears in East Croatia showed that the dominant species were F. graminearum, F. culmorum and F. avenaceum (Spanic et al 2010). The capability of Fusarium species to produce mycotoxins represents a potential risk to human and animal health (Nightingale et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In rainy periods, barley grains can be colorized with pink or red stains ( Figure 3). The consequences of Fusarium infection can be seen in yield decrease, lower average seed dimensions and a decrease in nutritive value-lower starch and proteins mass fractions, loss of colour, and changes in smell and taste of the grain [17,[33][34][35]. This disease classifies the grains as unacceptable and unsuitable for malting, even though all other quality parameters are acceptable for malting [27].…”
Section: Speciesmentioning
confidence: 99%
“…Most found species causing FHB in Central and Northern Europe are F. avanceum, F. graminearum, F. poae and F. culmorum (WG Smith) Sacc. [16][17][18]. There are several Fusarium species in Croatia: F. nivale, F. avanceum, F. culmorum and F. graminearum [19].…”
Section: Introductionmentioning
confidence: 99%